Immigrants' assimilation process in a segmented labor market - Miguel Angel Alcobendas; Núria Rodríguez-Planas (Institute for the Study of Labor (IZA), 2009)
While much of the literature on immigrants' assimilation has focused on countries with a large tradition of receiving immigrants and with flexible labor markets, very little is known on how immigrants adjust to other types of host economies. With its severe dual labor market, and an unprecedented immigration boom, Spain presents a perfect natural experiment to analyze immigrations' assimilation process. Using data from the 2000 to 2008 Spanish Labor Force Survey, we find that immigrants are more occupationally mobile than natives, and that much of this greater flexibility is explained by immigrants' assimilation process soon after arrival. However, we find little evidence of convergence, especially among women and high skilled immigrants. This suggests that instead of integrating, immigrants are occupationally segregating, implying that there is both imperfect substitutability and underutilization of immigrants' human capital.
urn:nbn:de:101:1-20091009957
Keywords: J15; J24; J61; J62; 330; Immigrants' assimilation effects; cohort effects; occupational distributions and mobility; segmented labor markets; Migranten; Berufliche Integration; Arbeitsmobilität; Arbeitsmarktsegmentierung; Spanien